A Constraint-Based Approach to Wine Tourism Market Segmentation. (May 2017) - Cho, Meehee; Bonn, Mark A.; Brymer, Robert A.
This study investigated wine tourism constraints from a market segmentation perspective to understand the potential importance they may have on preference and behavioral intentions to visit wine regions. Using constraints scales customized to the wine tourism context, a factor-cluster segmentation approach generated five homogenous subgroups: Highly Constrained, Cost & Time Conscious, Family Togetherness, Unmotivated, and Minimally Constrained. Analysis of variance tests indicated that preference and intentions to visit wine regions were significantly different among the five clusters. In particular, two cluster groups representing Minimally Constrained and Family Togetherness were found to offer the most utility for further wine tourism market segmentation research. Implications for all cluster groups regarding unique sociodemographic characteristics and behavioral intentions were discussed. This study provides future academic research opportunities pertaining to the application of wine tourism constraints scales. Destination marketing organizations can apply these findings toward the development of effective target market strategies.